1999
DOI: 10.1021/bi9827823
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis Studies of the FeSII Protein of Azotobacter vinelandii:  Roles of Histidine and Lysine Residues in the Protection of Nitrogenase from Oxygen Damage

Abstract: The Azotobacter FeSII protein, also known as the Shethna protein, forms a protective complex with nitrogenase during periods when nitrogenase is exposed to oxygen. One possible mechanism for its action is an oxidation state-dependent conformational interaction with nitrogenase whereby the FeSII protein dissociates from the MoFe and Fe proteins of nitrogenase under reducing conditions. Herein we report the construction and characterization of five site-directed mutants of the FeSII protein (H12Q, H55Q, K14A, K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Conformational protection is due to the formation of a complex between the FeSII (Shethna) protein and nitrogenase under high intracellular oxygen concentrations. In this complex, nitrogenase is inactive but transiently protected from damage by oxygen (10,13,21). Additional studies have shown that the function of the FeSII protein is of major importance for cell viability under carbon and/or energy limitation but only when cells are grown diazotrophically (12,14).…”
mentioning
confidence: 99%
“…Conformational protection is due to the formation of a complex between the FeSII (Shethna) protein and nitrogenase under high intracellular oxygen concentrations. In this complex, nitrogenase is inactive but transiently protected from damage by oxygen (10,13,21). Additional studies have shown that the function of the FeSII protein is of major importance for cell viability under carbon and/or energy limitation but only when cells are grown diazotrophically (12,14).…”
mentioning
confidence: 99%
“…A distinct way of protecting [Fe-S] clusters is shown by the FeSII protein of Azotobacter vinelandii. The FeSII, or Shetna protein, forms a complex with nitrogenase under periods of high oxygen exposure, thus protecting the essential [Fe-S] cluster from oxidation (16,17).…”
mentioning
confidence: 99%
“…Figure 6 shows that the cells have redundant mechanisms for protection against the toxicity of H 2 O 2 . Thus, the protection against H 2 O 2 and against the generation of HO˙can be accomplished by (i) elimination of O 2 ·Ϫ by SODs to inhibit reactions 1 and 3; (ii) elimination of H 2 O 2 by hydroperoxidases to inhibit reaction 2; (iii) chelation of free iron by iron-chelator or by specific DNA-binding proteins (e.g., Dpr and Dps in gram-positive and gram-negative organisms, respectively) (27,59) to inhibit reaction 2; (iv) use of specific [Fe-S]cluster protectors-e.g., (20) and the Shetna protein (FeSII) in Azotobacter vinelandii (35) to inhibit reaction 1; or (v) the repair of damaged DNA and other macromolecules (8). Data in Fig.…”
Section: Discussionmentioning
confidence: 99%